"Evaluation of Rubella IgG Antibodies among High School Girls in Uremia City" - F Nanbakhsh; S Salari-Lak; F Broomand; H Mohaddesi; MR Taravati; F hadori (Tehran University of Medical Sciences, 2003)
Rubella or German measles is a mild contagious disease in non-pregnant women, but in pregnant affected mother's possibility of fetus infection in the first twelve weeks of gestation is 80%. Between 13-14 weeks of gestation is 54% and by the end of the second trimester is 25%. If fetus gets infected severe anomalies will progress. At present no vaccination against rubella is begin envisaged by the National Immunization Program in Iran. Because of serious complications of the rubella in pregnancy, it's very important to determine the immune status of young girls at their pre-marriage age. Five hundred eighty nine high school girls were selected at random from different high schools and then a questionnaire was filled up. Blood samples were obtained and anti-rubella IgG titre was detected in each sera by using American Diaplus Diagnostics ELISA kits. From 589 samples 500 students (89.4%) showed positive and 89 students (15.1%) revealed negative results for anti-rubella IgG. Of all 63 students (10.69%) had previously been vaccinated against rubella. The results indicated that 15.1% of all students and 20.7% of precollege girls would be mothers, are seronegative. Comparison of these results with the conclusions obtained in other cities of Iran shows that it would be necessary to screen rubella IgG antibodies in premarriage young girls on other regions of country and vaccination against rubella could be considered as a part of National Immunization Program.